2008
DOI: 10.1123/jpah.5.3.359
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Parents’ and 12-Year-Old Children’s Sport and Vigorous Activity: The Role of Self-Esteem and Athletic Competence

Abstract: Background:The aims of this study were to investigate parent–child physical activity (PA) associations and whether children’s self-esteem or athletic competence mediates such associations.Methods:The study population comprised 1124 12-year-old children and their parents. Parents’ PA was assessed using the Baecke questionnaire and a question about sport participation. Children’s PA was assessed by questions about participation in sport and vigorous activities. The children’s self-esteem and athletic competence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 0 publications
3
36
2
2
Order By: Relevance
“…These findings are consistent with previous research conducted by Taylor et al, who found also a positive association between parental activity and child’s activity (r = .17-.28) [50]. Eriksson et al found similar associations of parent-child physical activity relationships between 12-year-olds and their parents [51]. Parental physical activity was also assessed with the HPAQ, while children’s physical activity was administered with general questions about sports participation and further vigorous activities.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are consistent with previous research conducted by Taylor et al, who found also a positive association between parental activity and child’s activity (r = .17-.28) [50]. Eriksson et al found similar associations of parent-child physical activity relationships between 12-year-olds and their parents [51]. Parental physical activity was also assessed with the HPAQ, while children’s physical activity was administered with general questions about sports participation and further vigorous activities.…”
Section: Discussionsupporting
confidence: 91%
“…Parental physical activity was also assessed with the HPAQ, while children’s physical activity was administered with general questions about sports participation and further vigorous activities. They conclude that the family environment is “[…] an important target for interventions to increase physical activity in children […]” [51]. In this connection, Dunton et al [52] suggested that joint physical activity in parent-child pairs could have health benefits for both children and parents, “[…] especially for girls, older children, older parents, and higher income families”.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is difficult to compare our results with the results of existing studies, we discovered, similar to studies based on objective and subjective monitoring of PA [10,11,12,13,14,15,16,20,21,56,57] and SED [14,20,58], a significant positive correlation between parents’ and children’s PA as well as between parents’ and children’s SED. Difficulties in comparing our findings with the results of other studies include differences in the number of monitored days, duration of daily monitoring of PA and SED, type of monitoring instruments, logbooks and questionnaires and the fact that some studies had data from only one parent, whereas others had data from both parents.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, family background may confound the association between motor proficiency in early life and physical activity in later life since longitudinal observational follow-up studies may be affected by unobserved confounding factors, such as the childhood environment. Many of the possible factors associated with physical activity seem to have their roots in childhood and family experiences (8, 9, 12, 34, 35, 39). Hence, familial factors could explain at least a part of the association between motor proficiency and physical activity.…”
Section: Introductionmentioning
confidence: 99%